Zero-Sequence Circulating Current Suppression in Multi-paralleled Three-Level NPC Inverters under Unbalanced Operating Conditions - Park, Jun Hyeok; Lee, Kyo Beum (5th IEEE Conference on Energy Conversion, CENCON 2021, 2021)
This paper presents methods for suppressing high-frequency (HF-) zero-sequence circulating current (ZSCC) generated by interleaved pulse width modulation (PWM) and low-frequency (LF-) ZSCC generated by inconsistent circuit parameters or inconsistent reference signals. In medium/h igh power applications, three-level neutral-point-clamped (NPC) inverters are used in parallel connection to obtain high power rating. In this parallel operation, interleaved PWM is used to improve the quality of the output current with a small filter inductor. However, ZSCC increases due to the small filter inductor. The proposed methods for suppression of HF-ZSCC generated by interleaved PWM are alternative phase opposite disposition (APOD) PWM based on carrier modulation and double-reference PWM (DRPWM) based on reference signal modulation. Additionally, the method that injects an optimized zero-sequence voltage (ZSV) when LF-ZSCC is generated is added to suppress HF-And LF-ZSCC simultaneously. The ZSCC suppression performance is proved by the simulation results.
Keywords: Alternative phase opposite disposition pulse width modulation; Circulating current; Double-reference pulse width modulation; Interleaved pulse width modulation; Neutral-point clamped inverters; Pulsewidth modulations (PWM); Reference pulse; Three-level neutral point clamped; Three-level neutral-point-clamped inverte; Zero sequence voltage; Zero sequences; Zero-sequence circulating current; Zero-sequence voltage; alternative phase opposite disposition (APOD) PWM; double-reference PWM (DRPWM); interleaved PWM; three-level neutral-point-clamped (NPC) inverter; zero-sequence circulating current (ZSCC); zero-sequence voltage (ZSV)